APPLICATION OF NUMERICAL MODELING TO PIPE LEAKS IN FLUID FLOW - Ilmah, Aurista Miftahatul; Syarifuddin, Arief; Risdianto, Anauta Lungiding Angga (Universitas Lampung, 2024)
Pipes are a medium used to move flowing fluids and are very dependent on pressure and speed. Leaks in pipes can cause physical loss of water. This can be caused by many things, one of which is a leak caused by a hole in the pipe which can disrupt the flow of water so that the flow of water or fluid will change, including the pressure and speed. A fluid flow can be visualized using simulation or mathematical modeling using finite differences. By using the GNU Octave application, namely numerical computing which can be accessed for free without a license which is used as data visualization, it can provide an overview of fluid flow including the occurrence of leaks in pipes, namely by visually representing the state of fluid flow when a leak occurs in a pipe. With this visualization, a fluid flow pattern is produced where leaks occur at several different points. From the research results, it was found that the pipe before it got a leak would be laminar, but when it got a leak, the fluid flow would become a fluid flow that switched to transitional fluid flow or turbulence. Apart from that, the placement of coordinate variations slightly affects the fluid flow line